In TFIIH, XPD helicase is exclusively devoted to DNA repair. - Jochen Kuper (Public Library of Science (PLoS), 2014)
The eukaryotic XPD helicase is an essential subunit of TFIIH involved in both transcription and nucleotide excision repair (NER). Mutations in human XPD are associated with several inherited diseases such as xeroderma pigmentosum, Cockayne syndrome, and trichothiodystrophy. We performed a comparative analysis of XPD from Homo sapiens and Chaetomium thermophilum (a closely related thermostable fungal orthologue) to decipher the different molecular prerequisites necessary for either transcription or DNA repair. In vitro and in vivo assays demonstrate that mutations in the 4Fe4S cluster domain of XPD abrogate the NER function of TFIIH and do not affect its transcriptional activity. We show that the p44-dependent activation of XPD is promoted by the stimulation of its ATPase activity. Furthermore, we clearly demonstrate that XPD requires DNA binding, ATPase, and helicase activity to function in NER. In contrast, these enzymatic properties are dispensable for transcription initiation. XPD helicase is thus exclusively devoted to NER and merely acts as a structural scaffold to maintain TFIIH integrity during transcription.